The Effect of Artichocke Leaves Meal on the Utilization of Dietary Energy for Broiler Chicks - Abdo, Zeinab M.A.; Radwan, Nadia L.; Selim, Nessrin A. (International Journal of Poultry Science, 2007)
The main target of this study was to evaluate artichoke leaves meal in broiler diets containing different energy levels (the strain requirement and lower energy level). In this study, a total number of 240 unsexed one day old Ross broiler chicks were distributed randomly and divided equally into eight experimental groups (in 3 replicates of 10 each). The experimental groups were 4 levels of artichoke leaves meal (0, 2, 4 and 6% of the diet, mainly of the corn) in each of two diets. The first diet contained the recommended strain requirement of energy (RE), while the second diet contained 200 kcal ME /kg diet lower energy level (LE). All diets were formulated to meet other nutrient requirements of the chicks according to the strain requirement. After 28 days of age all birds fed finisher diets (RE or LE) without artichoke. The chemical analysis of artichoke leaves meal showed that it had good nutritive value. It contains some amino acids, the highest were for the essential amino acids arginine (0.51%) and leucine (0.42%). Artichoke contents of cynarin and total flavonoids were 1.194 and 1.064%. The results of this study showed that, the artichoke leaves meal used in this experiment decreased both BW and BWG, decreased the amount of consumed feed during the 28 days of age, while removing of artichoke increased the feed intake (28-42 days of age), in addition; it deteriorated both the feed conversion values and EPEI as compared with the control (without artichoke). The interaction between diet energy level and artichoke level had no significant effect on broiler performance during the total experimental period. Incorporation of artichoke leaves meal, regardless to energy level, had no significant effects on carcass characteristics except abdominal fat pad (AFP) which was decreased, especially at 4% artichoke when incorporated in low energy diet. The energy level, artichoke level or the interaction had no significant effect on blood constituents, in general at 28 and 42 days of age. It was observed that artichoke increased blood proteins and decreased blood total lipids and blood cholesterol at 28 days of age. Diets containing RE improved the digestibility coefficients (P ≤ 0.05) of DM, OM, CP, EE, CF and NFE as compared to LE diets. Supplementation of artichoke at 2 and 4% of diet improved the utilization of all the nutrients, significantly except NFE which was improved numerically, compared to the two control groups (without artichoke). Results indicated that LE diets depressed total feed cost/kg BW and improved net revenue and economic efficiency compared to RE diets. Addition of artichoke increased total feed cost/kg BW and decreased net revenue and economic efficiency compared to the control diet. However 4% artichoke when added to LE diet gave the same relative economic efficiency value as that of the RE control diet.